Indicators of crisis development and financial behavior of subjects of the global economic system in crisis periods - G. F. Romashkina; D. F. Skripnuk; K. V. Andrianov (Модернизация, инновация, развитие)
Purpose: is to form evaluative indicators of crises based on the analysis of financial behavior of subjects of the global economic system during various crisis periods.Methods: quantitative and qualitative analysis of the crises’ periodization, according to evaluative indicators calculated on the World Bank data; retrospective, comparative analysis of the financial behavior of subjects of the global economic system were used. Results: evaluative indicators of crises are formed. Methods and approaches to the study of crises are systematized based on the analysis of the financial behavior of subjects of the global economic system in crisis periods. It is shown that the state of the balance of payments can be among the evaluative indicators of crises. The spikes of the oil prices can also anticipate a crisis. The gold rises in price during and immediately after crisis, serving as a reserve currency. In this time, there is a decrease in the scale of variation in the growth rates of indicators of money supply, companies’ market capitalization and domestic credit.Conclusions and Relevance: the identified evaluative indicators can act as a system of leading indicators of crisis processes, in conditions of an increase in the global economy volume and the intensifying instability of the global financial system. It is shown that the financial sector of the world economy is increasingly detached from the real sector. The financial sector and state institutions, using various risk reduction tools, transfer risks to the global economic system, which leads to the development of new rules of financial behavior of the subjects of the global economic system in crisis periods. It is proposed to consider the leading indicators of crisis processes as a system that can form the basic factors of financial behavior of subjects of the global economic system in crisis periods, determining the directions of stability of the world economic system. The strengthening of the influence of new technologies, including advanced information and communication technologies, in the context of expanding the diversity of models and systems of interaction of individual agents and institutional systems can both act as an unconditional engine of economic development and provokes the strongest crises in the global economic system.